Robotic-Arm Assisted Technology's Impact on Knee Arthroplasty and Associated Healthcare Costs - David J. Kolessar; Daniel S. Hayes; Jennifer L. Harding; Ravi T. Rudraraju; Jove H. Graham (Journal of Health Economics and Outcomes Research)
# Background The number of total knee arthroplasties (TKA) carried out globally is expected to substantially rise in the coming decades. Consequently, focus has been increasing on improving surgical techniques and minimizing expenses. Robotic arm–assisted knee arthroplasty has garnered interest to reduce surgical errors and improve precision.